Challenges and Opportunities of Higher Education Based on Islamic Boarding Schools - Firdaus, Muhammad Mirza (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
The existence of Pondok Pesantren (Islamic Boarding Schools) was the oldest Islamic educational institution in Indonesia. Islamic boarding schools did not only teach Islamic religious sciences, but also the values ​​of independence, mutual cooperation, solidarity and Ukhuwah Islamiyah. Islamic boarding schools were very important institutions in producing a generation with good morals. The education system and traditions in Islamic boarding schools had to be maintained, but it did not rule out the possibility to develop and follow the progress of the times in order to continue to show the existence of an educational institution that was competitive in the global era. Islamic boarding schools were inclusive educational institutions that had the potential to be able to open Islamic schools (madrasas) or formal schools. It was a fact that graduates of Islamic boarding schools had made a positive contribution to the progress of the nation. Such as the Lirboyo Kediri Islamic Boarding School which had existed since 1910 AD. This 100-year-old boarding school had opened various branches of Islamic boarding schools in Indonesia, formal education institutions to universities. Islamic Institute of Tribakti (IAIT) was a university under the auspices of the Lirboyo Islamic boarding school, Kediri. Historically, this college was inaugurated on October 25, 1966 AD, or 56 years since the establishment of the Lirboyo Islamic Boarding School, Kediri. The existence of this university was increasingly giving color to students, not only getting religious knowledge, but students also getting general sciences such as technology, economics, foreign languages, ​​and so on.